Prospects of the local Hubble parameter measurement using gravitational waves from double neutron stars. Issue 3 (10th January 2018) - Seto, Naoki; Kyutoku, Koutarou
Abstract: Following the detection of the GW170817 signal and its associated electromagnetic emissions, we discuss the prospects of the local Hubble parameter measurement using double neutron stars (DNSs). The kilonova emissions of GW170817, AT 2017gfo, are genuinely unique in terms of the rapid evolution of colour and magnitude, and we expect that, for a good fraction ≳ 50 per cent of the DNS events within ∼200 Mpc, we could identify their host galaxies, using their kilonovae. At present, the estimated DNS merger rate (1.5^+3.2_-1.2)× 10^-6 Mpc^-3 yr^-1 has a large uncertainty. But, if it is at the high end, we could measure the local Hubble parameter H L with the level of Δ H L / H L ∼ 0.049 (1σ level), after the third observational run (O3). This accuracy is four times better than that obtained from GW170817 alone, and we will be able to examine the Hubble tension at 1.8σ level.